CO2 abatement costs in China and BRI countries: From the perspective of technological heterogeneity - Hu, Shuo; Da, Yingzhu; Wang, Ailun (Frontiers in Energy Research, 2022)
As China cannot achieve its emission reduction target without cooperating with other countries, the international carbon trading market has become a part of China’s carbon trading market system. The Belt and Road Initiative (BRI) has brought many development opportunities to countries participating, but critics have also voiced concerns about the environmental and climate degradation it might bring. Thus China is making a great effort towards building a green and low-carbon BRI, part of which is a joint effort with other countries to cut greenhouse gas emission and achieve the 2,030 sustainable development goals. The estimation of abatement costs is the basis of regional carbon emission reduction cooperation and a prerequisite for establishing a regional carbon trading market. Taking into account the technological heterogeneity, this paper uses linear programming to estimate inefficiency level for China and BRI countries, and further calculates the marginal abatement cost (MAC) of carbon dioxide for each country. The results show that after considering technological heterogeneity, the average inefficiency level for China and BRI countries is 2.410%, which is about 26.526% lower than the traditional geographic grouping approach, indicating that the technological heterogeneity among BRI countries is significant and cannot be ignored. Most countries have a low inefficiency level, some countries show a clear trend. China has an average marginal abatement cost of 1440.183 USD/ton. As the marginal abatement cost varies greatly among countries, a large amount of abatement cost could be saved for China and BRI countries if the cost difference is exploited.